A Novel Drug-Drug Solid Dispersion Of Hydrochlorothiazide-Losartan Potassium - M.PANNEERSELVAM; R.NATRAJAN; S.SELVARAJ; N.N.RAJENDRAN (International Journal of Pharma and Bio Sciences, 2010)
To investigate the effect of a novel drug- drug solid dispersion approach on the dissolution of hydrochlorothiazide in a fixed dose combination with Losartan potassium. Solid dispersion of hydrochlorothiazide and losartan potassium (12.5mg: 50mg) was prepared by co-precipitation method. Solid dispersions were characterized by differential scanning calorimetry, x-ray diffractometry and dissolution tests and the results were compared with that of pure drugs and physical mixtures. Solid dispersion as well as physical mixture were then compressed into tablets and evaluated for physicochemical, stability and dissolution characteristics and the results compared with commercial tablets. Both solid dispersion and solid dispersion tablets of hydrochlorothiazide and losartan potassium showed an enhanced dissolution of hdrochlorothiazide compared with pure hydrochlorothiazide, physical mixture, and commercial tablets. The solubility of hydrochlorothiazide increased with increase in concentration of losartan potassium as observed from the phase solubility study. Stability study on the tablets showed no changes either in the drug content or in the dissolution profile. The results of present study suggest that the novel drug-drug solid dispersion approach is promising for improving dissolution of poorly soluble drugs presented in a fixed dose combination with soluble drugs